Revisiting the Phillips curve: Visualization from a multidimensional graphical perspective - Mario Arturo Ruiz Estrada; Su-Fei Yap; Noor Azina Binti Ismail (Contemporary Economics, 2017)
This article explores the possibility of visualizing the Phillips curve from a multidimensional perspective. We use a new multidimensional coordinate space, the mega-dynamic disks multivariable random coordinate space in vertical position, which visualizes the graphical behavior of the Phillips curve from a multidimensional point of view. We take A. W. Phillips's original paper published in Economica in 1958, 'The Relation between Unemployment and the Rate of Change of Money Wage Rates in the United Kingdom, 1861-1957,' as our main bibliographical reference. The same paper also serves as our main database for transforming the original Phillips curve into a multidimensional graphical form. In essence, our paper extends the significance of the Phillips curve beyond mere theory to serve as a practical instrument for solving economic problems.
Keywords: Y20; 330; Inflation; Unemployment; Phillips curve; Multidimensional coordinate spaces; Econographicology